Subjektwerden unter Bedingungen von outsiderness Subjektivierungstheoretische Lesarten kurdischer Schulbildungsbiographien in der Türkei - Hoppe, Marie (Verlag Barbara Budrich, 2023)
How do patterns of national inclusion and exclusion make themselves felt at school? What experiences do students have in their everyday school life? How are they shaped by these experiences? This empirical study examines processes of subjectivation in schooling biographies of young Kurdish women in Turkey and asks how relations of inclusion and exclusion in the nation-state are inscribed in subjects through school. It shows the relevance of processes of appropriation and resistance for the formation of self-conceptions in the face of natio-ethno-cultural (non-)belonging and closes with thoughts on marginalized agency.